Clinical effects comparison of different approaches and anterior attachment release methods in temporomandibular joint disc repositioning and anchoring surgery - WANG Hao, WANG Wei, LI Qiang, YAN Jiaxuan, NIE Wei, GUO Yanjun, YAN Wei, CHEN Yong (口腔疾病防治)
Objective To explore the therapeutic effects of different surgical methods for temporomandibular joint disc reduction and anchoring surgery, providing reference for optimizing this surgical procedure. Method The study was approved by the hospital ethics committee. 173 patients (195 joints) who underwent temporomandibular joint disc repositioning and anchoring surgery were selected for retrospective analysis. Patients were categorized into groups A (traditional preauricular incision-scalpel/tissue scissors anterior attachment release), 35 patients (40 joints), B (traditional preauricular incision-plasma bipolar radiofrequency electrode anterior attachment release), 42 patients (46 joints), C (revised tragus incision - scalpel/tissue scissors anterior attachment release), 50 patients (58 joints), and D (revised tragus incision-plasma bipolar radiofrequency electrode anterior attachment release), 46 patients (51 joints). After a 6-month postoperative follow-up, the differences in maximum mouth opening (MMO), visual analogue scale (VAS), effective rate of joint disc reduction, incidence of preauricular numbness, obvious scars among patients in each group at 1, 3, and 6 months were compared postoperatively. Results After surgery, the MMO of all four groups of patients initially shrunk and then gradually increased compared to before surgery. At the 1-month follow-up after surgery, the plasma bipolar radiofrequency release (B+D) group had a smaller impact on the patient’s MMO compared to the surgical knife/tissue scissors release (A+C) group (P < 0.05). Postoperative VAS scores for all four groups showed a gradual decrease from pre-operative levels, with the (B+D) group scoring significantly lower in the first month post-surgery compared to the (A+C) group (P < 0.05). Six months post-surgery, the rate of joint disc reduction of the four groups were higher than 95%, with no significant differences observed between the groups (P > 0.05). Patients in the revised tragus incision (C+D) group experienced a lower rate of preauricular numbness compared to those in the traditional preauricular incision (A+B) group (4.59% vs. 12.79%, P < 0.05), The incidence of obvious scars in the (C+D) group was significantly lower than that in the (A+B) group (3.67% vs. 23.26%, P < 0.05). Conclusion The revised tragus incision is superior to traditional preauricular incision in terms of protecting the auriculotemporal nerve and the scars were more inconspicuous. Further, the plasma bipolar radiofrequency electrode is superior to the scalpel/tissue scissors in terms of mouth opening recovery and pain control. For temporomandibular joint disc reduction and anchoring surgery, a modified tragus incision combined with plasma bipolar radiofrequency electrode to release the anterior attachment of the joint disc can be recommended as a surgical option.